2021
DOI: 10.36548/jtcsst.2021.2.003
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Finding Efficient Approach to Detect Customer Emotion Analysis using Deep Learning Analysis

Abstract: The role of facial expression recognition in social science and human-computer interaction has received a lot of attention. Deep learning advancements have resulted in advances in this field, which go beyond human-level accuracy. This article discusses various common deep learning algorithms for emotion recognition, all while utilising the eXnet library for achieving improved accuracy. Memory and computation, on the other hand, have yet to be overcome. Overfitting is an issue with large models. One solution to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Research results showed that the designed algorithm is superior to traditional machine learning algorithms in sentiment classification and comment rating prediction ( Luo and Xu, 2021 ). Kottursamy (2021) studied the role of facial expression recognition in social science and HCI, discussed various common deep learning algorithms for emotion recognition, and established a new CNN model based on the eXnet library to achieve higher facial recognition accuracy.…”
Section: Related Workmentioning
confidence: 99%
“…Research results showed that the designed algorithm is superior to traditional machine learning algorithms in sentiment classification and comment rating prediction ( Luo and Xu, 2021 ). Kottursamy (2021) studied the role of facial expression recognition in social science and HCI, discussed various common deep learning algorithms for emotion recognition, and established a new CNN model based on the eXnet library to achieve higher facial recognition accuracy.…”
Section: Related Workmentioning
confidence: 99%
“…e classifier outputs the final result of the integration in the form of an array. Since the research object is multiemotion classification, the content in the array represents the probability of multiple emotions in the text [27,28]. e softmax classifier calculates the probability that a sample belongs to a certain category as follows:…”
Section: Classification Outputmentioning
confidence: 99%
“…Thus, the domain of FER has been studied broadly for the past 10 years [5]. Currently, with the rise of appropriate data and continuous progression of deep learning (DL), a FER mechanism that precisely identifies facial expressions in several surroundings is being studied actively [6]. FER depends on an evolutionary and ergonomic technique.…”
Section: Introductionmentioning
confidence: 99%